The Role of Value Creating Education and Ubuntu Philosophy in Fostering Humanism in Africa - Odari, Masumi H. (Journal of Interdisciplinary Studies in Education, 2020)
Soka (value creating) education is a Japanese concept propounded by Tsunesaburo Makiguchi and further developed by Josei Toda and Daisaku Ikeda. This educational philosophy aims to foster individuals who can find meaning in their lives and contribute to the well-being of others to better society. Ubuntu, an African philosophy, espouses togetherness and collectivism. Like value creating education, Ubuntu promotes working for the good of all not solely the individual. Examining these two philosophies, this paper explored their role in promoting humanism. Focusing on the education system in Kenya, this paper investigated how the institutionalization of both philosophies can foster global citizens and realize a more humane Kenya. Furthermore, this paper illustrated the importance of educators as agents of change, aiding students to become global citizens who work towards building a more humanistic society. This paper concluded that integrating both value creating education and Ubuntu in the education system can serve as a tool to nurture individuals who will not only improve their quality of life but also contribute positively to promote a more just and prosperous world.